2019
DOI: 10.3892/ol.2019.9993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of sevoflurane and propofol anesthesia on pulmonary function, MMP‑9 and postoperative cognition in patients receiving lung cancer resection

Abstract: Effects of sevoflurane and propofol anesthesia on pulmonary function, matrix metalloproteinase-9 (MMP-9) and postoperative cognition were compared in patients undergoing simple resection of lower lobe of left lung. Retrospective method was used to analyze 58 cases of lung cancer patients treated by simple resection of lower lobe of left lung in the Second Hospital of Dalian Medical University from October 2016 to October 2017, and they were divided into two groups: Sevoflurane group (n=32) with sevoflurane ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 16 publications
(16 reference statements)
3
19
0
Order By: Relevance
“…In the present study, sevoflurane not only increased the transcription and translation of MMP-1, -2, and -9, but also increased NSCLC cell migration ability depending on the exposed dose. Consistent with our results, Wang et al [ 30 ] found that sevoflurane anesthesia during lung cancer surgery increased the serum MMP-9 level compared with propofol anesthesia. In contrast, in a study using A549 cells, another NSCLC cell line, Liang et al [ 31 ] demonstrated that sevoflurane inhibited MMP-2 and -9 expression and cancer cell invasion and migration in a dose- and time-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, sevoflurane not only increased the transcription and translation of MMP-1, -2, and -9, but also increased NSCLC cell migration ability depending on the exposed dose. Consistent with our results, Wang et al [ 30 ] found that sevoflurane anesthesia during lung cancer surgery increased the serum MMP-9 level compared with propofol anesthesia. In contrast, in a study using A549 cells, another NSCLC cell line, Liang et al [ 31 ] demonstrated that sevoflurane inhibited MMP-2 and -9 expression and cancer cell invasion and migration in a dose- and time-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, propofol induces cell apoptosis by increasing the expression level of p53 upregulated modulator of apoptosis in NSCLC (31). It has also been demonstrated that propofol decreases the expression of the inflammatory factor matrix metalloproteinase 9 and the cognitive impairment in patients undergoing lung cancer resection (32). Consistently, the present study demonstrated that propofol inhibited NSCLC cell proliferation and promoted NSCLC cell apoptosis.…”
Section: Mapk10 Expression -----------------------------supporting
confidence: 90%
“…Previous studies have reported a modest reduction in melatonin secretion on the first day following different types of surgery, such as orthopedic and abdominal, compared with pre-surgery levels, as well as a high increase in melatonin secretion on the second day following surgery (29,30). The decrease in melatonin and MMP-9 serum level one day post-surgery may be due to the effects of general anesthesia, particularly the administration of propofol (31,32). To eliminate the influence of propofol on the circadian rhythm of melatonin and MMP-9 in patients with OSCC in the present study, blood was collected on the second day post-surgery.…”
Section: Discussionmentioning
confidence: 99%